Penyuluhan ASI eksklusif pada ibu hamil di Desa Wirokerten Kabupaten Bantul pada masa pandemic COVID-19 - Tri Siswati; Aulia Putri Utami (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2020)
Early supplementary breastfeeding was cause of stunting. Health education was strategy to increase knowledge skills on exclusive breastfeeding. This was community empowerment to increase mother’s and community health worker’s understanding on exclusive breastfeeding. We facilitate online education by google meet and maintaining their knowledge by WhatsApp groups. Participants were 14 persons (mothers and cadres) in Wirokerten Village, Banguntapan, Bantul, DI Yogyakarta. The indicator output was participant attendance (minimum 80%), increasing of knowledge and interactive online discussions. This was conducted in January 2021 for two weeks. Overall, all of participant were attended (100%), discussion interacted, and knowledge increased by 17%. Online education is effective strategy to increase knowledge participants on exclusive breastfeed during COVID-19 pandemic.